Conyza bonariensis as an alternative host for Colletotrichum species in Argentina - Bonacci, Martín (2020)
Aims: This study investigated the diversity of Colletotrichum isolates recovered from Conyza bonariensis leaves through the use of morphological characteristics, growth rate, carbon sources utilization and phylogenetic analysis. Methods and Results: Thirty Colletotrichum isolates recovered from Conyza bonariensis leaves showing symptoms of disease were included in the present study. Based on the analysis of morphology and sequences, the isolates were distributed into six Colletotrichum species complexes. The concatenated alignment of GAPDH and ITS sequences showed that 20 out of 30 isolates were included in four species complexes which comprise the most important pathogens causing anthracnose in soybean or anthracnose and stalk rot in maize: C. truncatum, C. orchidearum, C. gloeosporioides and C. graminicola. The remaining ten isolates were included in the C. boninense and C. destructivum species complexes or could not be assigned to any complex with the available information. Conclusion: Weeds belonging to genus Conyza are host to soybean and maize potential pathogenic species of Colletotrichum and could have a role as inoculum reservoir for cross contamination in the agroecosystem. Significance and Impact of the Study: The combined use of morphological, kinetics and physiological parameters of growth and phylogenetic analysis in Colletotrichum isolates from Conyza leaves allowed the detection of species complexes previously not identified in Argentina.